Association between water, sanitation, general hygiene and oral hygiene practices of street-involved young people in Southwest Nigeria - Morenike Oluwatoyin Folayan; Mary O. Obiyan; Atinuke O. Olaleye (BMC, 2020)
Abstract Background Oral hygiene practices can be linked to personal hygiene practices, including access to water and other sanitation facilities. The objective of the study was to determine if there is an association between oral hygiene practices and water and sanitation hygiene (WASH) practices among street-involved young people (SIYP). Methods A cross-sectional study recruited SIYP age 10-24 years in two States in Nigeria recruited through respondent-driven sampling in December 2018. Interviewer-administered questionnaires were used to collect data on water access, sanitation, personal and oral hygiene. The instruments used for collecting the data were standardized tools for measuring the phenomena studied. The association between knowledge and practice of oral hygiene; oral hygiene and water, sanitation and hygiene (WASH); and indicators of good oral hygiene were determined using binary logistic regression guided by two models. Results A total of 845 study participants were recruited. The proportion of SIYP with good knowledge of oral hygiene was low (31.2%), and fewer had good oral hygiene practice (8.9%). There were significant associations between knowledge and practice of tooth cleaning, use of fluoride-containing toothpaste, dental flossing, consumption of sugar between meals, and frequency of dental check-ups (p < 0.001 respectively). Respondents with good water collection and storage practices (AOR: 2.01; 95% CI: 1.24-3.24; P = 0.005) and those residing in Lagos (AOR: 2.85; 95% CI: 1.61-5.06; P = 0.001) had a higher likelihood of having good oral hygiene. Conclusion Good oral hygiene practices of SIYP in Nigeria is associated with access to water collection and storage. WASH programs can have an impact on health through improved oral hygiene practices.